Modified task-based learning program promotes problem-solving capacity among Chinese medical postgraduates: a mixed quantitative survey - Yanping Tian (BMC Medical Education, 2017)
Abstract Background Despite great advances, China’s postgraduate education faces many problems, for example traditional lecture-based learning (LBL) method provides fewer oppotunities to apply knowledge in a working situation. Task-based learning (TBL) is an efficient strategy for increasing the connections among skills, knowledge and competences. This study aimed to evaluate the effect of a modified TBL model on problem-solving abilities among postgraduate medical students in China. Methods We allocated 228 first-year postgraduate students at Third Military Medical University into two groups: the TBL group and LBL group. The TBL group was taught using a TBL program for immunohistochemistry. The curriculum consisted of five phases: task design, self-learning, experimental operations, discussion and summary. The LBL group was taught using traditional LBL. After the course, learning performance was assessed using theoretical and practical tests. The students’ preferences and satisfaction of TBL and LBL were also evaluated using questionnaires. Results There were notable differences in the mean score rates in the practical test (P < 0.05): the number of high scores (>80) in the TBL group was higher than that in the LBL group. We observed no substantial differences in the theoretical test between the two groups (P > 0.05). The questionnaire results indicated that the TBL students were satisfied with teaching content, teaching methods and experiment content. The TBL program was also beneficial for the postgraduates in completing their research projects. Furthermore, the TBL students reported positive effects in terms of innovative thinking, collaboration, and communication. Conclusions TBL is a powerful educational strategy for postgraduate education in China. Our modified TBL imparted basic knowledge to the students and also engaged them more effectively in applying knowledge to solve real-world issues. In conclusion, our TBL established a good foundation for the students’ future in both medical research and clinical work.